Uji Kualitas Kadar Air Benih Jagung dengan Metode Kapasitif Berbasis Web - Ezhar Savero (Jurnal Jaringan Telekomunikasi, 2018)
In an effort to control the quality of corn, among others, it is determined based on the moisture content in the corn seeds so that the corn produced has a seed quality standard. The purpose of this thesis is to determine the water level of the seeds. Corn was tested by a tool made with standardization of the moisture content of corn seeds from the Agricultural Center using the PM-650 Grain Moisture Tester. The parameters tested were the moisture content of the corn seeds, the temperature of the storage containers, and the weight of the corn seeds. Based on the research that has been done, it can be seen that a capacitive sensor with a working principle such as a parallel plate capacitor as a tool for measuring the moisture content of corn seeds has a reading accuracy ratio with the PM-650 Grain Moisture Tester measuring instrument is 94.9%. The temperature in the storage container was around 23 <temperature <27 to maintain the quality of the corn seeds. Data from the test results are sent via the ESP8266 module and displayed on the web. Based on the results of the planning and implementation that has been done, the capacitive sensor can work well as a measuring tool for the moisture content of corn seeds. Meanwhile, the difference in results in planning and measurement is caused by the losses that exist in the components used.